Development of the psychological well-being scales - Prewnim, Arpakorn; Suksawang, Poonpong; Pradujprom, Piyathip (Thai Journal of Nursing, 2020)
The purpose of this research and development was to develop the Thai version of psychological well-being scales. A sample of 30 Thai citizens, was purposively selected. The index of item-objective congruence (IOC) and the Cronbach’s alpha coefficient were used in data analysis. The results were as follows. 1) The Thai version of psychological well-being scales-Multidimensional, comprised 84 items and 6 components; (1) autonomy, (2) environment mastery, (3) personal growth, (4) Positive relations with others, (5) purpose in life, and (6) Self-acceptance. 2) Its index of item-objective congruence (IOC) was 1.00, the Cronbach’s alpha coefficients of the psychological well-being scales in total and 6 subparts were 0.84, 0.85, 0.85, 0.82, 0.87, 0.88, and 0.79 respectively.